Longitudinal course and phenotypes of health‐related quality of life in adults with atopic dermatitis. (10th November 2021) - Schwartzman, G.; Lei, D.; Ahmed, A.; Chavda, R.; Gabriel, S.; Silverberg, J. I.
Summary: Background: The real‐world course of health‐related quality of life (HRQoL) in atopic dermatitis (AD) is not well established. Aim: To examine predictors, longitudinal course and phenotypes of HRQoL in adult patients with AD. Methods: This was a prospective dermatology‐practice based study of 955 patients with AD (age 18–97 years). Patients were assessed at baseline and approximately 6, 12, 18 and 24 months. HRQoL was assessed using the 10‐item short‐form Patient‐Reported Outcomes Measurement Information System (PROMIS) Global Health (PGH). AD severity and impact was assessed by patient‐reported global AD severity, Patient‐Oriented Eczema Measure (POEM), Eczema Area and Severity Index (EASI), Objective SCORing Atopic Dermatitis (O‐SCORAD), Investigator's Global Assessment (IGA), Numerical Rating Scale (NRS) average and worst itch, PROMIS sleep‐related impairment (SRI), and nine‐item Patient Health Questionnaire (PHQ)‐9. Repeated‐measures regression models were constructed to examine itch over time. Results: In multivariable linear regression models controlling for age, race/ethnicity, history of asthma, hay fever and food allergy, baseline PGH‐physical (PGH‐P4) T scores were inversely associated with patient‐reported global AD severity, POEM, EASI, objective SCORAD, IGA, NRS average and worst itch, PROMIS SRI and PHQ‐9, with stepwise decreases of physical health with worsening severity. PGH‐mental health (PGH‐M4) T scores were associated with all aforementioned severity measures aside from POEM. In multivariable repeated measures linear regression models, decreased PGH‐P4 and PGH‐M4 T scores and mapped five‐dimension EuroQoL over time were associated with self‐reported global AD severity, NRS worst and mean itch, POEM, PROMIS sleep disturbance and SRI, EASI, objective SCORAD, IGA and PHQ‐9. Latent class analysis identified six classes of HRQoL, which were associated with measures of AD severity, nonwhite race, Hispanic ethnicity and having only public health insurance, but not age or sex. Conclusion: Patients with AD have a heterogeneous longitudinal course and distinct patterns of HRQoL. Many patients had fluctuating HRQoL over time. Most patients with moderate to severe disease at baseline had persistent HRQoL impairment over time.